It’s not all about gender: A Multi-dimensional Course Perspective on Diversity and Inclusion in Software Engineering Education - Gama, Kiev; Santos, Reydne (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3531, 2024)
Diversity and inclusion (D&I) are topics that are increasingly being recognized as important in CS education. There are a few guidelines on approaching D&I in CS education courses. When narrowing down to Software Engineering (SE), the literature on approaching D&I in SE education is scarce. There has been recent growth in the SE field in the literature covering this topic, mostly around software teams. Still, most publications are not focused on education and are typically centered around gender. However, there are other important dimensions of diversity that remain underexplored, such as race/ethnicity, disability, neurodivergence, and age. This experience report details how we approached those diversity dimensions in a graduate school course – attended by both MSc and PhD students – on Diversity and Inclusion in Software Engineering. We explored two perspectives: users and teams, which relate to the subdomains of Software Requirements and Human Aspects of Software Engineering, respectively. In this course, classes were held remotely, using Google Meet, Discord, and Google Classroom as communication tools, and took place twice a week, with each meeting lasting 2 hours. Assessments were conducted using a formative approach, observing student participation and engagement throughout the semester. According to student feedback, creating a safe space was important for creating a sense of belonging and an ambiance for learning and sharing their experiences. We provide details on how we structured and conducted this course. In addition, we share lessons learned throughout this process.